Preservice Teachers’ Engagement with the Merdeka Curriculum: A Qualitative Study in a Pedagogy of Writing Course - Sakkir, Geminastiti; Jayadi, Karta; Sakkir, Rini Isnaeni; Wahyuni, Ika Yuli (Pascasarjana Universitas Negeri Makassar, 2025)
This study investigates how preservice English teachers at Universitas Negeri Makassar understand and implement the principles of the Merdeka Curriculum within the “Pedagogy of Writing” course. As a curriculum reform aimed at promoting student-centered, project-based learning and the development of 21st-century competencies, the Merdeka Curriculum requires significant pedagogical shifts, especially in writing instruction. A qualitative descriptive approach was employed to explore students’ conceptual and practical engagement with the curriculum. The participants included 210 fifth-semester students enrolled in the course during the 2022/2023 academic year. Data were collected through in-depth interviews, classroom observations, and document analysis, focusing on three representative lesson plans. Thematic analysis revealed that while students generally grasped key curriculum concepts such as learner autonomy and the Profil Pelajar Pancasila, their classroom implementation varied widely. Common challenges included limited instructional resources, time constraints during school-based practicums, and difficulties in aligning creative writing tasks with standardized assessments. Despite these obstacles, many students demonstrated innovation in instructional design and a willingness to reflect critically on their teaching practices. The findings highlight the need for more structured pedagogical support within teacher education programs to strengthen curriculum understanding and implementation. This study contributes to the growing literature on curriculum transformation in Indonesian higher education and offers insights for policymakers and curriculum developers seeking to enhance teacher preparation for 21st-century education.